Tardigrada from a sub-Andean forest in the Sierra Nevada de Santa Marta (Colombia) with the description of Itaquascon pilatoi sp. nov. - Lisi, Oscar; Londoño, Rosana; Quiroga, Sigmer (Zootaxa, 2014)
Currently only 32 species of limno-terrestrial tardigrades have been reported in the literature for Colombia. Our study focused on both heterotardigrades and eutardigrades, which were extracted from eight samples of bryophytes and lichens collected in a sub-Andean forest transect in the Sierra Nevada de Santa Marta, Colombia. Fourteen species were found, six of which are new records for Colombia: Echiniscus madonnae Michalczyk & Kaczmarek, 2006, Echiniscus virginicus Riggin, 1962, Milnesium krzysztofi Kaczmarek & Michalczyk, 2007, Doryphoribius amazzonicus Lisi, 2011, Isohypsibius sattleri (Richters, 1902) and Diphascon higginsi Binda, 1971; and one new to science. Itaquascon pilatoi sp. nov., is characterized by having smooth cuticle, no eyes, buccal tube almost as long as the pharyngeal tube, well developed, obvious stylet furcae with long branches, slender claws, no lunules and no cuticular bars on the legs. The new species differs from I. umbellinae Barros, 1939, the most similar species, in having the stylet supports inserted precisely at the border between buccal and pharyngeal tube, more slender claws and more pronounced length differential between the external and internal claws of each leg. The total number of Colombian limno-terrestrial tardigrade species is raised to 37.